Mapping and auditing digital literacy of civil servants in selected South African government departments - Blessing Mbatha (Communicare)
As digital technology becomes ubiquitous, workers will increasingly need an appropriate set of digital skills to access and process information, using digital systems and tools. Hence, the aim of the study was to map and audit the digital literacy of civil servants in selected South African government departments in KwaZulu-Natal (KZN). Through a survey, four government departments, considered to be central to service delivery, were targeted. To obtain a representative sample, a systematic sampling method was applied. Data were analysed using the SPSS statistical analysis programme. The results suggested that not enough is being done to equip civil servants with the digital literacy skills they require to improve service delivery. As technology changes, so does the need for training in new technologies. Developing digital literacy in the workplace is a definite way for businesses and organisations to increase their work productivity and creativity. It is important to note that digital literacy is an essential requirement for effective and optimal participation in the world’s economy. The digital era is not going to disappear, and the need for education to respond to the growing digital tide is rapidly increasing. A digitally literate workforce is crucial if government is serious about improving work productivity and creativity in the public sector.